Pengembangan dan Sosialisasi Mesin Penebar Pakan Ikan Terpadu dengan Aerator Jenis Kincir Air pada Petani Tambak - Rusdi Nur; Syaharuddin Rasyid (Jurnal Teknik Mesin Sinergi, 2010)
The Ipteks programs are based on several factors that can affect the success of fish culture in milkfish and shrimp ponds is the availability of pond water quality is suitable for fish life fish and shrimp. In the intensification of efforts, one of the decisive parameters in improving pond water quality is to regulate the provision of oxygen content in water and fish feeding an orderly and proper dosage. Dissolved oxygen is very important for respiration and is one of the main components in the metabolism of fish and shrimp and other aquatic organizations. In addition, the system of fish feeding on fish and shrimp have been still using the traditional system, are fish/shrimp given to spread as much as 2-3 times a day. This system has several shortcomings, namely: the amount of feed given was not uniform, the feed is not spread evenly, and farmers have the pond every day. With the feed spreader tool has been developed as a tool in addition to the feed as well as spreader aerator tool that can provide aeration to the water's surface, then we can overcome the above problems with the feeding arrangement, which automatically threw food on time and the desired dose, and the continuously rotating wheel aerator will provide a spark against the surface of the water so the fish will be closer to get a new oxygen.